The Effect of Augmented Reality-Assisted Spinner Learning Media on Science Learning Outcomes of Fifth Grade Students at MIN 2 Ngawi - Shofia Nur Lailatul Khoiriah; Aulia Fajar Khasanah; Miratu Chaeroh (Journal of Educational Sciences, 2026)
This study addresses the difficulty in visualizing abstract science concepts often leads to low student understanding and engagement in elementary science learning. Conventional teaching methods dominate, and interactive technology based media are limited. The research evaluated the effect of Augmented Reality (AR)-assisted spinning-wheel media (Spinner) on fifth grade students learning outcomes. Employing a quasi-experimental design with a nonequivalent control group. The study used purposive sampling to recruit 54 students, dividing them into experimental and control groups. Data were collected via a validated 20 item multiple choice test and analyzed using an independent samples t-test. The experimental groups average score significantly increased from 52.96 to 78.52, while the control group only improved from 45.93 to 58.89. Statistical analysis confirmed a significant difference between the two groups (p<0.05). These findings demonstrate that integrating AR with spinning media effectively improves learning outcomes in the Natural and Social Sciences (IPAS) subject. This study concludes that AR-assisted interactive media offers an innovative solution for enhancing conceptual understanding in elementary science learning. Therefore, AR-assisted learning media can serve as an innovative for improving conceptual understanding in primary science education.